Formulasi dan uji karakteristik tablet effervescent buah belimbing wuluh dengan variasi konsentrasi asam sitrat dan asam tartat - Ambarwati, Nadya; Nur, Fikria Marfuatin; Hidayah, Fufut Nurul (Journal of Pharmaceutical and Sciences, 2025)
Background: Averrhoa bilimbi L. is a natural source of vitamin C with potential as an antioxidant. Effervescent tablets are a popular dosage form in which the choice of acid sources, such as citric acid and tartaric acid, is critical due to their hygroscopic properties that affect the physical characteristics and stability of both granules and tablets. Objective: This study aimed to formulate and evaluate the effect of varying concentrations of citric acid and tartaric acid combinations on the physical characteristics of granules and effervescent tablets of Averrhoa bilimbi powder. Methods: The study employed the dry granulation method. Four tablet formulas with different ratios of citric acid and tartaric acid were prepared. The granules were evaluated for flowability, angle of repose, and moisture content. The resulting tablets were tested for organoleptic properties, weight uniformity, size uniformity, hardness, friability, and dissolution time. Data were statistically analyzed. Results: The evaluation showed that all granule characteristics (flow time 1.36–1.56 seconds; angle of repose 9.95°–13.50°; moisture content 3.298%–4.622%) met the requirements. All tablet evaluation parameters (weight uniformity, size uniformity, hardness, and dissolution time 1.27–1.36 minutes) also complied, except for friability (1.401%–2.832%), which exceeded the specified limit (>1%). Statistical analysis indicated that acid concentration variations had a significant effect (p-value < 0.05) on all tested parameters except tablet friability (p-value > 0.05). Conclusion: It can be concluded that variations in citric acid and tartaric acid concentrations significantly affect the characteristics of Averrhoa bilimbi effervescent granules and tablets, except for friability. The nonconformity observed in friability testing is presumed to be influenced by other formulation factors such as the type and concentration of binders and lubricants. Further studies on formula optimization, vitamin C content analysis, and accelerated stability testing are recommended.